P‐69: Studies on 2D/3D Switchable Autostereoscopic Display with Spatial and Sequential Hybrid Control Using PDLC Films. Issue 1 (May 2016) - Chen, Haiyu; Liang, Haowen; Zhang, Quanquan; He, Jieyong; Zhou, Jianying; Li, Juntao; Wang, Jiahui; Lin, Tsung Hsien; Khoo, Iam Choon
Abstract : An effective approach to achieve 2D/3D switching in an autostereoscopic display with spatial and sequential hybrid control (SSHC) using polymer dispersed liquid crystal (PDLC) films is proposed. The Monte Carlo method is utilized to analyze the scattering interaction of diffusive PDLC layer within the system. And the experimental result is given for a two‐viewpoint SSHC system. The results show that PDLC working as 2D/3D switch is fairly feasible in a directional backlight autostereoscopic display.